Megrment the Level of SDF1-Α in the Serum of Patients with Urinary Tract Infection and Patients with Vaginal Infection - Ahmed Abbas Ali, Hayder Hamzah Ibrahim (Pakistan Journal of Medical & Health Sciences, 2023)
Urinary tract infection, Bacterial vaginosis as one of the global threats affecting millions of women and causing some time deaths around the world. Objective: This study aims to assess levels of SDF1 and IgA in patients with Urinary tract infection, Bacterial vaginosis, and people enjoying good health as a control group. Methods: Collecting medical information from (180) participants in the Imam Al-Sadiq General Teaching Hospital in Iraq-Babylon, the Gynecology Consultant, according to specific criteria, the subjects were divided into three groups: the control group, the patients (UTI, BV), while the demographic study included age, education, Jobs, and living Laboratory results, signs and symptoms, SDF1-α and IgA levels were assessed by the enzyme-linked immunosorbent assay (ELISA) technique. Results: The results revealed that there were significant variations in SDF1 and IgA between the UTI group, BV group, and control groups. SDF1 level with the UTI group was (1.206522 ±.0927277 pg/ml) and for patients with BV was(1.213735 ±.0661389 pg/ml) whereas the control group appear was (1.130013±.0496400 pg/ml), IgA level in the UTI patients was (64.252983 ± 7.5946759pg/ml) and patients with BV was (60.441928±6.1457661pg/ml) whereas the control group appears was (48.011745 ±4.7938613 pg/ml) Conclusion: They can be considered good indicators to give knowledge about the diagnosis of urinary tract infection and bacterial vaginosis, and help doctors to give appropriate medications. Keywords: Urinary tract infection, bacterial vaginosis, stromal cell-derived factor 1-alpha, Immunoglobulin A.